1987
DOI: 10.1002/hep.1840070623
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron microscopic observations on the inflammatory infiltrates and HLA antigens in hepatitis B and non-A, Non-B

Abstract: The present knowledge of the inflammatory reaction occurring in situ during hepatitis B favors a T cell-dependent MHC-restricted immune response. However, the reports in the literature are primarily based on the application of monoclonal antibodies directed at different lymphocyte subsets which discern only lymphocytic phenotypes and do not reflect the actual situation adequately. Therefore, we investigated the liver biopsies of patients with hepatitis B (28 patients) and non-A, non-B (21 patients) by immunoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
1
2

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 17 publications
5
51
1
2
Order By: Relevance
“…1). In inflammatory states of the liver, hepatocytes can upregulate MHC class II 6 and consequently gain the ability to interact with CD4 ϩ T cells and Treg too. In addition to LSEC and KC, we found that hepatocytes also induce suppressive activity of Treg (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In inflammatory states of the liver, hepatocytes can upregulate MHC class II 6 and consequently gain the ability to interact with CD4 ϩ T cells and Treg too. In addition to LSEC and KC, we found that hepatocytes also induce suppressive activity of Treg (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 Indeed, the most prevalent professional APC in liver, liver sinusoidal endothelial cells (LSEC) and Kupffer cells (KC), 2,3 have been shown to actively induce immune tolerance. 2,4,5 In addition, hepatocytes, which can upregulate expression of class II molecules of the major histocompatibility complex (MHC II) during hepatitis 6 and may then serve as APC for CD4 ϩ T lymphocytes, 7 also have been implicated in the induction of immune tolerance. 8 Nevertheless, rapid infiltration of the liver with inflammatory cells is induced during infection.…”
mentioning
confidence: 99%
“…At 1,4,6,24, and 48 hours after Con A injection, the liver was perfused first with phosphate buffered saline for 30 seconds and then with either 2% paraformaldehyde in 0.1 mol/L phosphate buffer, pH 7.4, or 1.5% glutaraldehyde in 0.067 mol/L cacodylate buffer, pH 7.4, plus 1% sucrose for 3 minutes via the portal vein. A part of the liver specimen was immersed in 10% formalin for 1 week, and serial paraffin sections 4-µm thick were cut and stained with hematoxylin and eosin (H-E).…”
Section: Animalsmentioning
confidence: 99%
“…1,2 Lymphocyte attachment to the endothelial cells of central veins and portal veins, termed ''endothelialitis'', 3 and lymphocyte migration into the subendothelial layer are common features seen in inflammatory human liver diseases. 4 However, the mechanism and locational heterogeneity of lymphocyte adhesion and transmigration in the hepatic vasculature are poorly understood.…”
mentioning
confidence: 99%
“…The number of NK cells is increased during the acute phase of hepatitis; however, during various chronic liver diseases, the NK cell population is diminished. [2][3][4]7 The importance of NK cells in the early stage of infection was demonstrated in NK-deficient mice (bg/bg mice) or mice depleted of NK cells by treatment with a specific antibody. These animals became more susceptible to murine cytomegalovirus infection.…”
mentioning
confidence: 99%